Steady state and time-resolved fluorescence studies of a hemagglutinin from Moringa oleifera - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (Journal of Fluorescence, 2008)
The saccharide binding and conformational characterization of a hemagglutinin, a low molecular weight protein from the seeds of Moringa oleifera was studied using steady state and time resolved fluorescence. The lectin binds sugars LacNAc (K-a = 1380 M-1) and fructose (K-a = 975 M-1), as determined by the fluorescence spectroscopy. It has a single tryptophan per monomer which is exposed on the surface and is in a strong electropositive environment as revealed by quenching with iodide. Quenching of the fluorescence by acrylamide involved both static (K-s = 0.216 M-1) and collisional (K-sv= 8.19 M-1) components. The native protein showed two different lifetimes, tau(1) (1.6 ns) and tau(2) (4.36 ns) which decrease and get converted into a single one, (2.21 ns) after quenching with 0.15 M acrylamide. The bimolecular quenching constant, k(q) was 7.55 x 10(11) M-1 s(-1). ANS binding studies showed that the native protein has exposed hydrophobic patches which get further exposed at extreme acidic or alkaline pH. However, they get buried in the interior of the protein in presence of 1 M GdnHCl or urea.
Keywords: ANS binding; fluorescence; Hemagglutinin; lifetime; Moringa oleifera; saccharide binding; Solute quenching

Structure-activity relationship of a hemagglutinin from Moringa oleifera seeds - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2008)
The hemagglutinin from the seeds of Moringa oleifera (MoL) agglutinates human as well as rabbit erythrocytes; the affinity for the latter is almost 250 times more than that for the former. MoL was inhibited by glycoproteins namely thyroglobulin, fetuin and holotransferin indicating the complex sugar specificity of the lectin. The protein is a homodimer with molecular mass of 14 kDa, subunits (7.1 kDa) linked by the disulfide bond(s). The secondary structure elements of MoL area-helix, 28%; beta-sheet, 23%; turn 20% and unordered 28%. While the activity and secondary structure were not affected at extreme pH and high temperature, they were drastically affected in presence of dithiothreitol at and above pH 7.0, indicating that disulfide linkages hold the active conformation of the protein. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: disulfide linkages; Moringa oleifera hemagglutinin; Secondary structure